2021
DOI: 10.1021/acssuschemeng.1c05589
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Stress-Gated Electromagnetic Interference Shielding Fabrics with Real-Time Adjustable Shielding Efficiency

Abstract: Traditional electromagnetic interference (EMI) shielding films generally have constant shielding efficiencies that cannot respond to the real-time changing shielding requirements of smart wearable electronics. Here, we report a stress-gated EMI shielding fabric with a high elastic strain of 470% that exhibits variable shielding performance by stretching the fabric to different deformations. The fabric is fabricated through electroless plating Cu nanoparticles on the electrospun polyurethane nanofiber films, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…However, the ε’’ and µ’’ values were relatively low, indicating a difficulty in transferring the electric and magnetic field forces [ 53 ]. The as-prepared fabrics exhibited a weak conductive ability, as shown in Figure 7 d,e, which could be attributed to the magnetite NdFe 2 O 4 NPs’ low interior motion of the magnetic dipole in varying magnetic fields for transferring electric fields, thus supporting the results in Figure 7 b,c [ 54 ]. In comparison with the existing samples, the fabrics with different NPs had little difference in their specific capacitance ( Cp ) values and dielectric constants.…”
Section: Resultssupporting
confidence: 71%
“…However, the ε’’ and µ’’ values were relatively low, indicating a difficulty in transferring the electric and magnetic field forces [ 53 ]. The as-prepared fabrics exhibited a weak conductive ability, as shown in Figure 7 d,e, which could be attributed to the magnetite NdFe 2 O 4 NPs’ low interior motion of the magnetic dipole in varying magnetic fields for transferring electric fields, thus supporting the results in Figure 7 b,c [ 54 ]. In comparison with the existing samples, the fabrics with different NPs had little difference in their specific capacitance ( Cp ) values and dielectric constants.…”
Section: Resultssupporting
confidence: 71%
“…For further comparison purposes, published research articles [32][33][34][35][36][37] for state-of-the-art externally tunable shielding responses are shown in Fig. 10 and the corresponding EMI SE values are summarized in Table S2 in the ESI.…”
Section: Effect Of Moisture On Shielding Performancementioning
confidence: 99%
“…Additionally, the BFSM sample in the absence of a porous structure demonstrates a lower SE T value (Figure S3). The comparisons among BFL 1.8 SM 30 samples and typical EMI shielding materials with respect to shielding performances are shown in Figure d, and it is observed that the BFL 1.8 SM 30 sample has a superior SE T value in the reported references. ,, …”
Section: Resultsmentioning
confidence: 96%